Antibacterial Activity of Schiff Base Chelates of Divalent Metal Ions - Baiu, S.H.; El-Ajaily, M.M.; El-Barasi, N.M. (Asian Journal of Chemistry, 2010)
Some new chelates of Mn(II), Co(II), Cu(II) and Cr(III) ions with Schiff base derived from salicylaldehyde and thiourea have been synthesized and investigated by elemental analysis, molar conductance measurements, infrared and electronic spectra. The elemental analysis data exhibited the formation of 1:1 [M:L] ratio. The obtained molar conductance values revealed that all the chelates are non-electrolytic in nature. The infrared spectral data showed the chelateation behaviour, which is through to the nitrogen and oxygen atoms of the ligand. The electronic absorption spectral data displayed the existence of π-π*, n-π* (HC=N) transitions and the expected geometrical structures. By testing the effects of these Schiff base ligands on five species of bacteria (S. aureus, K. pneumoniae, E. coli, P. aeruginosa and P. mirabilis) in vitro, it has been found that Mn(II) chelate was very effective, Co(II) chelate had moderate effect and no effect of Cu(II) chelate was found on these bacteria. The effects of Mn(II) and Co(II) chelates increased with higher concentrations.